(untitled) (Research, Society and Development, 2022)
This is a systematic review protocol, whose objective is to identify and analyze risk factors for HIV infection among young people. The review will be conducted through the following steps: elaboration of the research question, search for relevant publications, selection of studies found, data extraction, analysis, and evidence synthesis. The guiding question was elaborated from the PEO strategy (person, exposure and outcome): what are the risk factors (E) for HIV infection (O) among young people (P)? For bibliographic search, controlled and free vocabularies that address the question to be investigated will be used. The searches will be carried out in seven scientific literature databases and one gray literature database, in addition to a manual search for articles. The results obtained will be exported to the Rayyan QCRI software, allowing the exclusion of duplicate materials and the reading of titles and abstracts by two reviewers independently. Observational-analytic studies that address risk factors associated with HIV infection among young people will be included in the study, and those included will be read in full to ensure their applicability to the study. The data found will be extracted through a structured form so that they are then subjected to a narrative synthesis and meta-analysis, if possible. Studies will also be subjected to an assessment of methodological quality and, finally, the quality of the evidence will be analyzed.